PENGARUH PENURUNAN TARIF PPH, SANKSI PAJAK DAN MODERNISASI PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM JAKARTA BARAT SELAMA PANDEMI COVID-19 - Carisa Natascha; Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research targets at how the impact of the very last PPH discount, tax sanctions, and tax service modernization on taxpayer compliance of west Jakarta MSMEs throughout the covid-19 pandemic. The purposive sampling method became used for this sample and the entire legitimate information turned into a hundred Respondents. The processing strategies the usage of a couple of regression evaluation information helped by using the SPSS software (Statistical Product and provider answer) for windows released 20 and Microsoft Excel 2013. The results of this have a look at implying that final PPH reduction, tax sanctions, and tax service modernization have effective effects on taxpayer compliance. The implication may be given as an enter and know-how approximately taxes and wish that by using the information this is given in the thing of tax compliance ought to help the authorities to elevate tax incomes.